Immobilization and molecular interactions between bacteriophage and lipopolysaccharide bilayers - Handa, Hitesh (Langmuir : the ACS journal of surfaces and colloids, 2010)
The paper describes immobilization methods of bacteriophage P22 and tailspike gp9 proteins isolated from P22 on atomic force microscope (AFM) probes. The paper also reports single molecule force spectroscopy (SMFS) using AFM of the immobilized P22 (or gp9) interactions with substrate-supported O-antigenic lipopolysaccharides (LPS) bilayers. LPS covers the outer membrane of gram-negative bacteria, such as Salmonella typhimurium. Evidence from AFM imaging and SMFS shows that immobilized P22 (or gp9) are capable of strong and multivalent binding to supported LPS. The most common rupture forces between P22 and LPS were identified to be 72, 130, 206, and 279 pN at force loading rate of 12,000 pN/s. The quantized unbinding force was found to decrease with decreasing force loading rate as predicted by the Bell model. By fitting the force data with the Bell model, an energy barrier of 55 kJ/mol was obtained. Evidence is also provided that demonstrates the resilience of phage to pH and temperature fluctuation as well as dehydration/rehydration cycles. The biospecific interactions between P22 and the LPS are relevant to cell infection, inflammation, cancer progression and metastasis, food safety, pharmaceuticals, and biosensor development